Perlindungan Hukum Terhadap Buruh Pada Sistem Hukum Sistem Kerja Di Negara Kepulauan Indonesia - Muhammad Rafli Akbar Fahriza; Dewa Gede Pradnya Yustiawan (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This article aims to establish Legal safeguards for employees.within the legal framework of the employment system in Negara kepulauan Indonesia. The study utilizes normative legal research with a focus on legal and regulatory methodologies.. The research findings demonstrate that legal protection for workers in the realm of the Negara kepulauan Indonesian employment system includes: 1) Compensation protection, social protection, and social guarantees for workers; 2) Security and health protection for activities; 3) Legal protection in establishing and becoming a workers' union or employee union; 4) Preventing the infringement of workers' rights in negotiations; in the private sector.